Jawabanmu

2014-03-10T08:11:17+07:00
a.-3/4×=-3/8
sederhanakan terlebih dahulu
jadi, 3x = 3/2
         x = (3/2) : 3
         x = 3/3 . 2
         x = 2
b.-x/5-3/5=5

-x/5 = 25/5 + 3/5
(nb: 25/5 dr 5 yang penyebutnya disamakan)
-x/5 = 28/5
-x = 28
x = 28/-1
x = -28
2014-03-10T08:19:09+07:00
a.-3/4×=-3/8
sederhanakan terlebih dahulu
jadi, 3x = 3/2
         x = (3/2) : 3
         x = 3/3 . 2
         x = 2

b.-x/5-3/5=5

-x/5 = 25/5 + 3/5
(nb: 25/5 dr 5 yang penyebutnya disamakan)
-x/5 = 28/5
-x = 28
x = 28/-1
x = -28